An improved hourly-resolved NOx emission inventory for power plants based on continuous emission monitoring system (CEMS) database: A case in Jiangsu, China. (1st October 2022) - Gu, Xuan; Li, Baojie; Sun, Chu; Liao, Hong; Zhao, Yongqi; Yang, Yang
Abstract: High-resolved emission inventories are essential to evaluate air quality and health effects. However, for one of the most polluting industries in China – power plants, emission uncertainties remain high due to the limitation of point measurements. In this study, we established an hourly NOx emission inventory based on the continuous emission monitoring system (CEMS) network of Jiangsu, China, with an integrated new method that coupled unit-level fuel consumption and emission factors. To evaluate the accuracy of our method, we compared the accuracies of our method to three other bottom-up inventories and determined that, our results (CEMS(Improved) for which the normalized mean bias (NMB) was 3.24%) exhibited higher accuracies compared to the other two methods: BASE EIs and CEMS(Traditional), for which the NMB was −38.53% and 294.1%, respectively. The total NOx emissions of power plants in Jiangsu, China, were 43701 tons in 2018, equivalent to 42.2% of that in 2017. 53% of total emissions were contributed by the southern Jiangsu area and super units (>1000 MW) exhibited the largest emissions shares (70%). The daily, monthly, and hourly average emissions demonstrated a "high in winter and summer" pattern. The ratio of the highest daily emissions in the June-July-August period (JJA) to the lowest in the September–November period (SON) was 1.20, which is relatively higher than that of fuel consumption (1.18) and power generation (1.15). The weekly and monthly emissions on hourly trends varied consistently, with peaks at 12:00, 16:00, 19:00, and 21:00 (except for high-discharge months). The hourly emissions on holidays and weekends were 6.4% and 1.6%, lower than those of workdays and weekends, with emission disparities being the largest in the period of 8:00–10:00. Our new hourly CEMS emission inventory can significantly reduce the uncertainties of emission estimation and better serve policy-making for mitigating power plant emissions in China. Graphical abstract: Image 1 Highlights: New hourly NOx emission inventory for power plants was established using CEMS data. The accuracy of our method was much higher than traditional emission inventories. The total NOx emissions of Jiangsu power plants declined rapidly to only 43701 t. Hourly emission patterns were analyzed on varied temporal scales.